2021
DOI: 10.1186/s12284-021-00522-8
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Structure Feature of the Aboveground and Belowground Microbial Community Respond to Drought in Wild Rice (Oryza longistaminata)

Abstract: Background Drought is global environmental stress that limits crop yields. Plant-associated microbiomes play a crucial role in determining plant fitness in response to drought, yet the fundamental mechanisms for maintaining microbial community stability under drought disturbances in wild rice are poorly understood. We make explicit comparisons of leaf, stem, root and rhizosphere microbiomes from the drought-tolerant wild rice (Oryza longistaminata) in response to drought stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 81 publications
(112 reference statements)
1
17
0
Order By: Relevance
“…These results are consistent with the research findings of Stouvenakers (Stouvenakers et al, 2020 ). Microbial diversity and interaction among ecological compartments of plants are related to their ability to resist external disturbance (Kusstatscher et al, 2019 ; Xie et al, 2021 ). In this study, the alpha diversity in the Chinese chive rhizosphere was significantly higher than that in other ecological compartments, the rhizosphere microbial network average degree and average clustering coefficient were higher than those in other ecological compartments, and the interaction of the microbial network was more complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with the research findings of Stouvenakers (Stouvenakers et al, 2020 ). Microbial diversity and interaction among ecological compartments of plants are related to their ability to resist external disturbance (Kusstatscher et al, 2019 ; Xie et al, 2021 ). In this study, the alpha diversity in the Chinese chive rhizosphere was significantly higher than that in other ecological compartments, the rhizosphere microbial network average degree and average clustering coefficient were higher than those in other ecological compartments, and the interaction of the microbial network was more complex.…”
Section: Discussionmentioning
confidence: 99%
“…As key nodes Proteobacteria and Firmicutes in the phylloplane ecological compartment, they are also key nodes in the root endosphere ( Figure 5 ). Rhizosphere microorganisms could enter the roots of Chinese chives, and some endophytic bacteria migrated from the root endosphere of Chinese chives to the upper stems and leaves (Edwards et al, 2015 ; Xie et al, 2021 ). There were some differences in diversity, bacterial composition, interaction network, and function among the microorganisms in the phylloplane, leaf endosphere, and stem endosphere of Chinese chives ( Figures 1 , 2 , 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate extremes can reorganize networks of associations between co-existing soil microbial taxa (Zhou et al, 2011;de Vries et al, 2018;Bardgett and Caruso, 2020;Yuan et al, 2021) with essential feedback on plant resilience and performance in stress environments. For example, recent studies have shown that WD significantly influences microbial co-existence networks (de Vries et al, 2018;Zhang et al 2021;Xie et al, 2021). These changes in the microbial co-existence network potentially impact the recovery of microbial communities and alter plant-microbe interactions under disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…A 16S rRNA gene amplification was performed for archaea and bacteria. Barcoded primers targeting the variable V4 regions of the 16S rRNA genes were used for amplification using the universal primer pairs, 515F (GGACTACNVGGGTWTCTAAT) and 806R (GGAC-TACHVGGGTWTCTAAT) [72][73][74][75]. Forward and reverse primers were tagged with Illumina adapter, pad, and linker sequences.…”
Section: Dna Extraction and 16s Rrna Gene Sequencingmentioning
confidence: 99%